2012
DOI: 10.1055/s-0032-1329892
|View full text |Cite
|
Sign up to set email alerts
|

A Radiological Comparison of Anterior Fusion Rates in Anterior Lumbar Interbody Fusion

Abstract: Aim To compare anterior fusion in standalone anterior lumbar interbody fusion (ALIF) using cage and screw constructs and anterior cage–alone constructs with posterior pedicle screw supplementation but without posterior fusion. Methods Eighty-five patients underwent single- or two-level ALIF procedure for degenerative disk disease or lytic spondylolisthesis (SPL). Posterior instrumentation was performed without posterior fusion in all cases of lytic SPL and when the anterior cage used did not have anterior scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Previous work has shown reduced fusion rate by stand-alone anterior approaches (ALF) compared to combined ALF with PLF. Combining ALIF with pedicle screw fixation for 1 to 2 level lumbar fusion has been shown to raise fusion rate from 65% to 100% at mean follow-up of 19 months, 14 and similarly high fusion rate (97%) in patients with stand-alone ALIF using posterior pedicle fixation with a follow-up of 2 years. 15 This analysis may confirm these findings, showing stand-alone anterior approaches are associated with increased reoperation rate—particularly within the first year following fusion.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work has shown reduced fusion rate by stand-alone anterior approaches (ALF) compared to combined ALF with PLF. Combining ALIF with pedicle screw fixation for 1 to 2 level lumbar fusion has been shown to raise fusion rate from 65% to 100% at mean follow-up of 19 months, 14 and similarly high fusion rate (97%) in patients with stand-alone ALIF using posterior pedicle fixation with a follow-up of 2 years. 15 This analysis may confirm these findings, showing stand-alone anterior approaches are associated with increased reoperation rate—particularly within the first year following fusion.…”
Section: Discussionmentioning
confidence: 97%
“…3 6 7 9 10 11 18 19 However, other studies showed superior union rates for instrumented ALIFs combined with posterior fixation, demonstrating that, although ALIF fixation with an anterior plaque or cage-integrated screws significantly increases stability, it is still inferior compared with the posterior instrumentation. 20 21 22 23 24 25 Moreover, the additional stability offered by posterior fixation or interbody fusion may probably contribute to decrease the intensity or even avoid symptoms in case of a nonunion ALIF, allowing these lack of fusions to be tolerated or asymptomatic. Further large randomized prospective studies are required to prove the effectiveness and safety of instrumented ALIF cages without additional stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…3 6 7 9 10 11 18 19 No entanto, outros estudos demonstram taxas de união superiores para as ALIFs instrumentadas combinadas com fixação posterior e que, apesar de a fixação da ALIF com placa anterior ou com parafusos integrados na caixa aumentar de forma significativa a estabilidade da construção, essa continua a ser inferior à obtida com a instrumentação posterior. 20 21 22 23 24 25 Além disso, a estabilidade adicional oferecida pela fixação ou artrodese posterior pode provavelmente contribuir para diminuir a intensidade ou mesmo evitar o aparecimento de sintomas na presença duma não união da ALIF, permite que essas não uniões sejam bem toleradas ou mesmo assintomáticas. Consideramos necessários mais estudos prospetivos aleatorizados de grande dimensão de modo a comprovar a eficácia e segurança das caixas de ALIF instrumentadas sem necessidade de estabilização posterior.…”
Section: Discussionunclassified
“…20 However, the success rate observed in these studies is not as high in more extensive arthrodeses, and so it is not recommended without additional posterior supplementation. 21 The observation of both growth and solid bone fusion has been put in check because of the lack of a simple and direct correlation with better clinical outcomes. However, complementary to this discussion, evolution with instability, migration of the device, or pseudoarthrosis may indeed be deleterious in certain cases.…”
Section: Discussionmentioning
confidence: 99%